Edwin Booth a biography and performance history - Bloom, Arthur W. 1939- (McFarland, 2013)
"Edwin Booth began his career in 1849 as teenager. This biography traces his life and career as a tragic actor, including his childhood; his early acting tours; his rise to fame; his two marriages; his relationship with his brother John Wilkes Booth. Includes extensive appendix detailing every known Edwin Booth performance, with reviews and other materials"..